Comparable Outcomes with Total Ankle Arthroplasty and AAA - Rizzo, Toni (MD Conference Express, 2014)
End-stage ankle arthritis is a disabling condition, with similar morbidity, pain, and loss of function as hip arthritis. Open ankle arthrodesis (OAA) has been the gold standard for treatment of end-stage ankle arthritis, but better outcomes have been obtained with arthroscopic ankle arthrodesis (AAA). The aim of the study discussed in this article, was to compare the outcomes of total ankle replacement, AAA, and OAA in patients with isolated, nondeformed ankle arthritis.